Relationship of two vertical jumping tests to sprint and change of direction speed among male and female collegiate soccer players - McFarland, I. T.; Dawes, J. J.; Elder, C. L.; Lockie, R. G. (Sports, 2016)
Abstract: In collegiate level soccer acceleration, maximal velocity and agility are essential for successful performance. Power production is believed to provide a foundation for these speed qualities. The purpose of this study was to determine the relationship of change of direction speed, acceleration, and maximal velocity to both the counter movement jump (CMJ) and squat jump (SJ) in collegiate soccer players. Thirty-six NCAA Division II soccer players (20 males and 16 females) were tested for speed over 10 and 30 m, CODS (T-test, pro agility) and power (CMJ, SJ). Independent t-tests (p = 0.05) were used to derive gender differences, and Pearson`s correlations (p = 0.05) calculated relationships between the different power and speed tests. Female subjects displayed moderate-to-strong correlations between 30 m, pro agility and T-test with the CMJ (r = -0.502 to -0.751), and SJ (r = -0.502 to -0.681). Moderate correlations between 10 and 30 m with CMJ (r = -0.476 and -0.570) and SJ (r = -0.443 and -0.553, respectively) were observed for males. Moderate to strong relationships exist between speed and power attributes in both male and female collegiate soccer players, especially between CMJ and maximal velocity. Improving stretch shortening cycle (SSC) utilization may contribute to enhanced sport-specific speed.